A Taguchi method application for the part routing selection in generalised group technology. (9th February 2009) - Hachicha, Wafik; Masmoudi, Faouzi; Haddar, Mohamed
Cellular manufacturing (CM) is an important application of group technology (GT) that can be used to enhance both flexibility and efficiency in today's small-to-medium lot production environment. The crucial step in the design of a CM system is the cell formation (CF) problem that involves grouping parts into families and machines into cells. The CF problem is increasingly complicated if parts are assigned with alternative routings (known as generalised GT problem). In most of the previous works, the route selection problem and CF problem were formulated in a single model, which is not practical for solving large-scale problems. We suggest that a better solution could be obtained by formulating and solving them separately in two different problems. The aim of this case study is to apply the Taguchi method to the route selection problem as an optimisation technique to get back to the simple CF problem, which can be solved by any of the numerous CF procedures. In addition, the main effect of each part and analysis of variance (ANOVA) are introduced as a sensitivity analysis aspect that is completely ignored in previous research. The case study results provided a better CF solution compared with Kusiak's solution.